Isolasi dan Identifikasi Methicillin Resistant Staphylococcus aureus dan Methicillin Resistant Staphylococcus pseudintermedius pada Kasus Klinis Anjing dan Kucing di Yogyakarta - Alhadz, Ghias Ghifari; Salasia, Siti Isrina Oktavia; Yosyana, Alyaa Rifqoh Putri; Wasissa, Madarina; Lestari, Fajar Budi; Widayanti, Rini (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus pseudintermedius (MRSP), are known as bacterial resistant to various antibiotics. MRSA transmission occurs between humans and direct human contact with dogs and cats. This study aimed to isolate, characterize, and analyze bacterial resistance to antibiotics phenotypically and genotypically from clinical case samples of pet animals in Yogyakarta. Bacterial isolates were identified through biochemical tests and molecular identification by species-specific 23S rRNA and nuc genes with polymerase chain reaction (PCR) and pta genes with PCR-restriction fragment length polymorphism (RFLP). Bacterial resistance to several antibiotics was analyzed using disk diffusion Kierby-Bauer method. The occurrence of methicillin resistance were screened by oxacillin resistance screening agar base (ORSAB) and confirmed by detection of the mecA gene with PCR. Based on the phenotypic and genotypic identification showed that 11 samples were identified as S. aureus (6 isolates) and S. pseudintermedius (5 isolates). The resistance tests revealed that 36% were resistant to tetracycline, cefoxitin (27%), oxacillin and erythromycin (9%). Screening of methicillin resistance with ORSAB indicated that all isolates were methicillin resistances (100%). Detecting the mecA gene encoding methicillin resistance showed that 81.81% of isolates were resistant to methicillin, with detail S. aureus (all 6 isolates) and S. pseudintermedius (4 isolates). Based on the antibiogram, ORSAB, and mecA gene detection, it could be confirmed that three isolates were MRSP, and six isolates were MRSA. The results of this study indicate the high occurrence of methicillin-resistant strains in pets that have the potential zoonotic spread to other animals and humans.